High‐Current‐Density Organic Electrochemical Diodes Enabled by Asymmetric Active Layer Design. Issue 7 (10th January 2022) - Kim, Youngseok; Kim, Gunwoo; Ding, Bowen; Jeong, Dahyun; Lee, Inho; Park, Sungjun; Kim, Bumjoon J.; McCulloch, Iain; Heeney, Martin; Yoon, Myung‐Han
Abstract: Owing to their outstanding electrical/electrochemical performance, operational stability, mechanical flexibility, and decent biocompatibility, organic mixed ionic–electronic conductors have shown great potential as implantable electrodes for neural recording/stimulation and as active channels for signal switching/amplifying transistors. Nonetheless, no studies exist on a general design rule for high‐performance electrochemical diodes, which are essential for highly functional circuit architectures. In this work, generalizable electrochemical diodes with a very high current density over 30 kA cm −2 are designed by introducing an asymmetric active layer based on organic mixed ionic–electronic conductors. The underlying mechanism on polarity‐sensitive balanced ionic doping/dedoping is elucidated by numerical device analysis and in operando spectroelectrochemical potential mapping, while the general material requirements for electrochemical diode operation are deduced using various types of conjugated polymers. In parallel, analog signal rectification and digital logic processing circuits are successfully demonstrated to show the broad impact of circuits incorporating organic electrochemical diodes. It is expected that organic electrochemical diodes will play vital roles in realizing multifunctional soft bioelectronic circuitry in combination with organic electrochemical transistors. Abstract : An asymmetric design of the organic mixed ionic–electronic conductor layer allows for the rectification of input signals with a high current density of over 30 kA cm −2 in an aqueous electrolyte. The operation mechanism is elucidated with the help of numerical analysis and in operando electrochemical potential mapping methods, and analog/digital circuits are demonstrated as a proof‐of‐concept of these novel device architectures.